2022
DOI: 10.1007/s00706-022-02964-2
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-based digital image colorimetry for the determination of vancomycin in drugs

Abstract: A simple smartphone-based digital image colorimetry is proposed for the determination of vancomycin in drugs. The analytical method relied on the reaction of vancomycin with copper(II) in ethanol–water medium with pH 4.3. The reaction resulted in the formation of a blue–grey complex, presenting an absorption maximum at 555 nm. A mobile application was used for smartphone-based analysis to decompose the individual channels of the colour model representations. The determination was performed using three smartpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…In biomedical applications, one of the notable areas SDIC has been applied is the quantification of the drug's active pharmacologic ingredients [54] and point-of-care antibiotic residual [54]. Mermer and colleagues reported standardization experiments on an SDIC method for the determination of vancomycin (antibiotics) content in drugs based on the colorimetric reaction of vancomycin with copper(II) in an acidic pH [55]. Exploring the simplicity of SDIC, James and Honeychurch [56] described the colorimetric determination of acetaminophen via its reduction of ferricyanide to give ferrocyanide, which is further converted to Prussian Blue upon the addition of iron(III), as shown in Figure 6.…”
Section: Application Of Smartphone Digital Image Colorimetrymentioning
confidence: 99%
“…In biomedical applications, one of the notable areas SDIC has been applied is the quantification of the drug's active pharmacologic ingredients [54] and point-of-care antibiotic residual [54]. Mermer and colleagues reported standardization experiments on an SDIC method for the determination of vancomycin (antibiotics) content in drugs based on the colorimetric reaction of vancomycin with copper(II) in an acidic pH [55]. Exploring the simplicity of SDIC, James and Honeychurch [56] described the colorimetric determination of acetaminophen via its reduction of ferricyanide to give ferrocyanide, which is further converted to Prussian Blue upon the addition of iron(III), as shown in Figure 6.…”
Section: Application Of Smartphone Digital Image Colorimetrymentioning
confidence: 99%
“…Quantitative analysis of many antibiotics like vancomycin, gentamicin, neomycin sulfate resazurin, etc. has also been carried out using smartphone-based colorimetric techniques (32)(33)(34). However, it is reported that the images captured from a smartphone suffer from the effects of ambient light and may lead to poor accuracy (35).…”
Section: Introductionmentioning
confidence: 99%